2017
DOI: 10.1111/rec.12600
|View full text |Cite
|
Sign up to set email alerts
|

Small mammal abundance and seed predation across boundaries in a restored‐grazed woodland interface

Abstract: Passive restoration is an effective tool for the maintenance and conservation of biodiversity. Often areas in recovery are immersed in a matrix of land uses, in which the expansion and intensification of human activities exert new visible pressures at their boundaries. The degree of connectivity between these areas and their peripheral lands can be analyzed by mobile link species, organisms that actively move in the landscape by connecting areas to one another through their functional roles. We focus our desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 77 publications
1
4
0
1
Order By: Relevance
“…Once soil restoration is achieved, plant restoration can proceed, actively or passively. The passive restoration of plant species is an emerging strategy for restoring native communities with minimal costs (Hobbs & Cramer, 2008;Tabeni et al, 2017). Moreover, the removal of grazing was an effective strategy for passive restoration in drylands, similar to the findings from a recent global grazing meta-analysis (Filazzola et al, 2020).…”
Section: The Outcome Of Active Vs Passive Restoration Practicessupporting
confidence: 64%
“…Once soil restoration is achieved, plant restoration can proceed, actively or passively. The passive restoration of plant species is an emerging strategy for restoring native communities with minimal costs (Hobbs & Cramer, 2008;Tabeni et al, 2017). Moreover, the removal of grazing was an effective strategy for passive restoration in drylands, similar to the findings from a recent global grazing meta-analysis (Filazzola et al, 2020).…”
Section: The Outcome Of Active Vs Passive Restoration Practicessupporting
confidence: 64%
“…Graomys griseoflavus, Akodon dolores, Eligmodontia typus, Calomys musculinus and Microcavia maenas) practice food hoarding, making both larderhoards and scatter-hoards with different effects on seed survival (Campos et al, 2007(Campos et al, , 2017Giannoni et al, 2013). In this relationship among P. flexuosa and its assemblage of dispersers, previous studies have shown that quantitative aspects of SDE directly related to animal visits and fruit removal are affected by changes in habitat heterogeneity under different land uses (Campos et al, 2016;Bessega et al, 2017;Tabeni et al, 2017;Miguel et al, 2017Miguel et al, , 2018a. Although the development of the SDE model for P. flexuosa began years ago, using an approach that combines field and laboratory experiments, the aim of the present study is to provide data to fill in some gaps in the model.…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study agree with previous publications which found, also using camera trapping, that G. griseoflavus is the main species removing Prosopis fruits in the Ñacuñán Reserve. The implications of fruit removal by G. griseoglavus in this fenced protected area were widely discussed, as well as the differential contribution of mammal species and functional groups to fruit removal in protected areas under different management interventions (Campos et al., ), in grazed landscapes (Miguel et al., ), and at sites connecting protected and grazed areas (Tabeni, Miguel, Campos, & Cona, ). In this sense, it was found that opportunistic frugivores and scatter‐hoarders become important as fruit removers in grazed areas and unfenced reserves, probably due to the effect of large herbivores, including domestic animals, on habitat complexity.…”
Section: Discussionmentioning
confidence: 99%